2023
DOI: 10.1021/acs.jafc.2c08221
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanism of Increased IgG/IgE Reactivity but Decreased Immunodetection Recovery in Thermally Induced Shrimp (Litopenaeus vannamei) Tropomyosin via Multispectroscopic and Molecular Dynamics Simulation Techniques

Abstract: Despite the fact that tropomyosin (TM) has highly stable structural characteristics, thermal processing can adversely influence its immunodetection, and the mechanism involved has not been elucidated. Purified TM was heated at various temperatures, and then the IgG/IgE-binding capacity and immunodetection recovery were determined; meanwhile, the structural alterations were analyzed via spectroscopic and molecular dynamics simulation techniques. The obtained results demonstrated that heat-treated TM showed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Shrimp has become a prevalent allergic food owing to its high consumption and delicacy properties, and exposure to shrimp allergen could trigger food allergic reactions among some consumers. 2 With the growing consumption of shrimp, the incidence of food allergy induced by shrimp has also shown an upward trend. The main allergen in shrimp is tropomyosin (TM), which is responsible for at least 80% of the allergic reactions that are induced by shrimp.…”
Section: Introductionmentioning
confidence: 99%
“…Shrimp has become a prevalent allergic food owing to its high consumption and delicacy properties, and exposure to shrimp allergen could trigger food allergic reactions among some consumers. 2 With the growing consumption of shrimp, the incidence of food allergy induced by shrimp has also shown an upward trend. The main allergen in shrimp is tropomyosin (TM), which is responsible for at least 80% of the allergic reactions that are induced by shrimp.…”
Section: Introductionmentioning
confidence: 99%
“…44 HIS in plasma was mainly produced by mast cells or basophils and was one of the crucial indicators of the degree of allergy. 45 As shown in Figure 3C, the HIS level in the ISP group was significantly increased to (74.45 ± 6.34) ng/mL (P < 0.05), which was 122.90% higher compared to the BC group. The HIS level was significantly lower in the ISPH group as (65.08 ± 3.37) ng/mL than that in the ISP group (P < 0.05).…”
Section: Effect Of Enzymatically Hydrolyzed Isp On Allergicmentioning
confidence: 78%
“…At the same time, INF-γ and IL-10 mediated immune cell responses, and there was an antagonistic relationship between Th1 and Th2 type cytokines. 45 From Figure 3F,G, INF-γ lungs, and jejunum were performed to observe the effect of enzymatic hydrolysis treatment on pathological changes in ISPsensitized mice. As depicted in Figure 4, the spleen, lungs, and jejunum of the BC group were in normal morphological conditions, and no obvious pathological changes were observed.…”
Section: Effect Of Enzymatically Hydrolyzed Isp On Allergicmentioning
confidence: 99%
“…Additionally, 142 peptides in HOVA and 189 peptides in HOVA-PP′ cut off the predicted linear epitopes. Allergic reaction was mainly due to the adverse reaction caused by the binding of antigenic epitopes in antigens to specific antibodies, , and PEF-assisted Alcalase treatment significantly reduced the antigenic epitopes in HOVA-PP′. Previous studies have shown that PEF treatment inhibited OVA-induced allergic reactions to some extent by altering the conformational epitopes of OVA.…”
Section: Resultsmentioning
confidence: 96%